Immune activation and microenvironmental crosstalk in hairy cell leukemia - Tanzeem, Hammad; Vick, Eric J. (Frontiers in Immunology, 2026)
Hairy cell leukemia (HCL) is an indolent leukemic B-cell malignancy that typically presents with pancytopenia and splenomegaly. Many patients achieve durable initial remissions with nucleoside analogs but ultimately relapse as leukemic cells acquire or exploit resistance mechanisms. Central to this resistance is the highly specialized leukemic microenvironment, particularly within bone marrow and splenic niches where hairy cells persist despite clearance of circulating disease. These protective niches provide CXCR4- and adhesion-dependent retention signals, cytokine support, and immune-evasion mechanisms that sustain leukemic survival, promote minimal residual disease, and ultimately drive relapse. In this Mini Review, we summarize how stromal interactions, extracellular-matrix remodeling, and disrupted immune surveillance reinforce therapeutic resistance in HCL, and how BCR and MAPK signaling interact with these circuits. Further, we highlight emerging strategies, including agents that disrupt chemotaxis, adhesion, and immune checkpoints, designed to dismantle microenvironmental support and improve the depth and durability of remission in HCL.